2013
DOI: 10.1111/1574-6968.12334
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SEM and VPSEM imaging techniques with respect toStreptococcus mutansbiofilm topography

Abstract: The study compared images of mature Streptococcus mutans biofilms captured at increasing magnification to determine which microscopy method is most acceptable for imaging the biofilm topography and the extracellular polymeric substance (EPS). In vitro S. mutans biofilms were imaged using (1) scanning electron microscopy (SEM), which requires a dehydration process; (2) SEM and ruthenium red (SEM-RR), which has been shown to support the EPS of biofilms during the SEM dehydration; and (3) variable pressure scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 29 publications
(46 reference statements)
3
39
0
1
Order By: Relevance
“…Evaluation of intact biofilm architecture by VPSEM and CSLM provides valuable information on cells and ECM spatial organization. VPSEM preserves the ECM since it does not require sample dehydration processes and high chamber vacuum [28]. The images showed that while the WT strain presented a typical bulky biofilm architecture encased by ECM material (Figure 2(b,c)), the Δ/Δ efg1 mutant strain was morphologically distinct from the WT (Figure 2(e,f)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of intact biofilm architecture by VPSEM and CSLM provides valuable information on cells and ECM spatial organization. VPSEM preserves the ECM since it does not require sample dehydration processes and high chamber vacuum [28]. The images showed that while the WT strain presented a typical bulky biofilm architecture encased by ECM material (Figure 2(b,c)), the Δ/Δ efg1 mutant strain was morphologically distinct from the WT (Figure 2(e,f)).…”
Section: Discussionmentioning
confidence: 99%
“…Variable-pressure scanning electron microscopy (VPSEM) protocol After 48 h of biofilm formation, the samples were transferred directly to the VPSEM (Zeiss EVO 50; Carl Zeiss Microscopy, LLC, Thornwood, NY, USA) chamber and imaged at 100 Pa. VPSEM images were captured at working distances of 6.5 mm and 7.0 mm and field widths of 10 µm and 20 µm [28].…”
Section: Wspmentioning
confidence: 99%
“…Cells were pelleted by centrifugation at 4,500 g for 5 min, washed twice and resuspended in phosphate-buffered saline (PBS). An aliquot (5.0 μl) of bacterial suspension was deposited on a clean sterile glass slide and air-dried at 37 ° C. Samples were fixed overnight in 2.50% glutaraldehyde solution, rinsed twice with PBS and dehydrated in a graded series of ethanol solutions (35.00, 50.00, and 75.00% for 30 min each; then two cycles of 90.00 and 100.00% for 30 min each) [Weber et al, 2014]. Samples were desiccated, sputter-coated with gold, and observed on a scanning electron microscope (Inspect F; FEI, Eindhoven, The Netherlands) at 20.0 kV.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…All specimens were first mounted on aluminum stubs and sputter-coated with gold (∼10–12 nm thickness) using a BAL-TEC SCD 050 sputter coater (Wetzlar, Liechtenstein/Vienna, Austria). Observations were made with a JEOL JSM-7001 Field Emission Scanning Electron Microscope (Jeol, Peabody, MA, USA) operating at 15 kV and using magnifications up to 2500X (Weber et al, 2014). …”
Section: Methodsmentioning
confidence: 99%